Milkchecker, As An Alternative Tool To Detect Subclinical Mastitis - Mirnawati Sudarwanto (Media Veteriner, 1997)
Two hundred and thirty milk samples of different quarters taken from dairy cows around Bogor and Cipanas were used in this study. The milk samples were tested aseptically against subclinical mastitis using the MC and AMP in the field and in the laboratory. The amount of leucocytes were counted using the BREED method.Using the MC the sensitivity is 85.2% and the specificity is 97.8% in detecting subclinical mastitis. In comparing the use of MC to the AMP or to the BREED method no significant difference was found. The MC should be used routinely to detect mastitis especiallynew for cases of subclinical mastitis.